15+6x=25+5x

Simple and best practice solution for 15+6x=25+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+6x=25+5x equation:


Simplifying
15 + 6x = 25 + 5x

Solving
15 + 6x = 25 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
15 + 6x + -5x = 25 + 5x + -5x

Combine like terms: 6x + -5x = 1x
15 + 1x = 25 + 5x + -5x

Combine like terms: 5x + -5x = 0
15 + 1x = 25 + 0
15 + 1x = 25

Add '-15' to each side of the equation.
15 + -15 + 1x = 25 + -15

Combine like terms: 15 + -15 = 0
0 + 1x = 25 + -15
1x = 25 + -15

Combine like terms: 25 + -15 = 10
1x = 10

Divide each side by '1'.
x = 10

Simplifying
x = 10

See similar equations:

| 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 | | 6x+3=x-6 | | 5y+2(y-4)=5(y+1)-2 | | 4(y+1)+5=(y-1)+y |

Equations solver categories